Pizacris: a new genus and two new species of Luzarinae cricket close to Guabamima de Mello, 1992 and Mellopsis Mews & Sperber, 2010 (Orthoptera: Grylloidea: Luzarinae) - Souza-Dias, Pedro G. B.; Desutter-Grandcolas, Laure; Pereira, Marcelo Ribeiro (Zootaxa, 2015)
Here we describe a new genus and two new species of Luzarinae crickets (Grylloidea, Phalangopsidae) from the Brazilian Atlantic Forest of Espírito Santo, Minas Gerais and Rio de Janeiro States (Brazil). We describe Pizacris Souza-Dias & Desutter-Grandcolas, n. gen., transfer the species Mellopsis zefai Mews & Sperber, 2010 to P. zefai (Mews & Sperber, 2010) n. comb., redescribe this species based in topotypes and, since the type series is lost, designate a neotype. We also describe the second species of this genus, P. carioca Desutter-Grandcolas & Souza-Dias n. gen., n. sp. The new genus is characterized by the dark brown uniform coloration with strikingly white joints 4 and 5 of maxillary palpi, reduced FWs, without stridulatory file and, mainly, the absence of the pseudepiphallic arms in male phallic complex. We provide a brief discussion about the morphology of male genitalia in Pizacris Souza-Dias & Desutter-Grandcolas, n. gen. and related genera, Guabamima de Mello, 1992 and Mellopsis Mews & Sperber, 2010. We also provide an identification key for these genera and notes about the reproductive behavior of P. zefai (Mews & Sperber, 2010) n. comb.